Sharia-Based Marketing Strategy: Ethical Approach and Market Segmentation in Improving Service Quality and Consumer Satisfaction - Sy. Amirah Nur Adilah Al-Aidid; Muhammad Alkaff (Universitas Islam Internasional Darullughah Wadda'wah, 2026)
The dynamics of the modern economy require Islamic financial institutions, such as Pegadaian Syariah, to integrate ethical and fairness principles into their marketing strategies in order to address issues of uncertainty (gharar) and conventional profit maximization. This research is urgent due to the challenges in developing market segmentation that is in line with consumers' spiritual values amid low Islamic finance literacy. The purpose of this study is to analyze the ethics-based marketing strategy and market segmentation applied by the Dompu Branch of Pegadaian Syariah in order to improve service quality and customer loyalty. This study uses a qualitative-descriptive approach with data collection techniques in the form of in-depth interviews, observations, and documentation of management and marketing staff. The results show that the product strategy (rahn syariah) eliminates the element of usury and is reinforced by ZIS services, as well as transparent and fair ('adl) pricing. Market segmentation focused on psychographic dimensions (religiousness and morality) proved effective in increasing customer retention. Promotion was directed as intensive education to overcome misconceptions, although low literacy remains a major challenge. The conclusion shows that this strategy has succeeded in building loyalty through value (ethical) alignment and transparency, providing a practical contribution in the form of a value-based sharia marketing model at the regional level.